Politics first: Examining the practices of the multi-district superintendent - Hall, Daniella; McHenry-Sorber, Erin (Education Policy Analysis Archives, 2017)
Over the past decade, multiple states have implemented a form of regional school district consolidation referred to as multi-district unions. Their organizational structure enables districts to retain individual school boards within regional local education agencies, all of which are overseen by a superintendent and a central board. However, no empirical research has been conducted to date on the ensuing work of multi-district superintendents. In our exemplary case study, we analyze time records, interviews, and observations to understand the role allocations and work of one multi-district superintendent. We find the division of time and ensuing responsibilities of the multi-district superintendent is predominantly political to the organizational structure of the union, and we conclude with implications for policy and practice.